Eating habits and eating disorders during pregnancy. - Fairburn, C; Stein, A; Jones, R (1992)
A general population sample of 100 primigravid women was studied prospectively to describe the changes in eating that occur in pregnancy with particular reference to cravings and aversions and the behavior and attitudes characteristic of clinical eating disorders. Assessment was by standardized interview. Dietary cravings and aversions were found to be common and largely confined to early pregnancy. Eating disorder features decreased in severity early in pregnancy but increased later on. Dietary cravings rarely resulted in episodes of overeating like those seen in patients with eating disorders. In this study of a general population sample, no evidence was found of a relationship between pregnancy outcome and the severity of eating disorder features prior to pregnancy.